The Limits of Community: Deconstructing the White Framing of Racist Speech in Universities. (November 2019) - Moore, Wendy Leo; Bell, Joyce M.
This article identifies the dominant frame through which university administrators in the United States respond to racist incidents and analyzes that from using the lens of critical race theory (CRT). We argue that the stock response of college and university administrators, which calls for counterspeech as the only appropriate response to racist speech, fails to consider the harmful effects of racist speech on students, staff, and faculty of color. Furthermore, this abstract-liberalist, color-blind approach decontextualizes racist speech from the historical and contemporary reality of structural racism that informs the speech acts and symbols used in these displays. We further use the CRT approach by shifting the perspective from a unilateral focus on protecting the right to racist speech to explore what happens when analysts focus instead on protecting substantively equal access for community members of color. In so doing, we highlight the value of CRT for revealing how white racial framing obscures competing legal and policy norms.